The Big Five Personality Models' Personality Types' Effects on State Civil Apparatus Performance - Saprudin Saprudin; Kumba Digdowiseiso (Universitas Sultan Ageng Tirtayasa, 2024)
Personality plays a crucial role in shaping an individual's behavior in different situations, including in the realm of public sector employment like the State Civil Apparatus (ASN). The objective of this research is to make a significant contribution to our comprehension of the interplay between ASN personality and performance. This study examines the influence of personality traits, particularly Extroversion, Introversion, Neuroticism, and Agreeableness, on ASN in the public sector. The primary objective is to comprehend the impact of the interplay among these dimensions on communication aptitude, collaboration, the ability to handle stress, and proficiency in fulfilling ASN responsibilities. The methodology employed is a comprehensive review of existing literature. The research findings indicate that this distinctive amalgamation of personalities plays a substantial role in team dynamics, adaptability to change, and efficacy in handling stress and pressure. ASN communication and collaboration skills are influenced by extroversion or introversion. Comprehending these dynamics enables management to create well-rounded teams, leveraging the strengths of extroverts in fostering connections and networking, while capitalizing on the introspective nature of introverts to offer profound insights. The findings suggest that managers should consider implementing training programs and human resource management strategies that specifically target the development of communication, collaboration, and stress management skills in individuals with ASNs. To summarize, an in-depth understanding of personality dimensions is crucial for attaining success in the dynamic work environment of the public sector.